Community-based mental health treatments for survivors of torture and militant attacks in Southern Iraq: a randomized control trial. Issue 1 (December 2015) - Weiss, William; Murray, Laura; Zangana, Goran; Mahmooth, Zayan; Kaysen, Debra; Dorsey, Shannon; Lindgren, Kristen; Gross, Alden; Murray, Sarah; Bass, Judith; Bolton, Paul
Abstract Background Systematic violence is a long-standing problem in Iraq. Research indicates that survivors often experience multiple mental health problems, and that there is a need for more rigorous research that targets symptoms beyond post-traumatic stress (PTS). Our objective was to test the effectiveness of two counseling therapies in Southern Iraq in addressing multiple mental health problems among survivors of systematic violence: (1) a transdiagnostic intervention (Common Elements Treatment Approach or CETA); and (2) cognitive processing therapy (CPT). The therapies were provided by non-specialized health workers since few MH professionals are available to provide therapy in Iraq. Methods This was a randomized, parallel, two site, two-arm (1:1 allocation), single-blinded, wait-list controlled (WLC) trial of CETA in one site (99 CETA, 50 WLC), and CPT in a second site (129 CPT, 64 WLC). Eligibility criteria were elevated trauma symptoms and experience of systematic violence. The primary and secondary outcomes were trauma symptoms and dysfunction, respectively, with additional assessment of depression and anxiety symptoms. Non-specialized health workers (community mental health worker, CMHW) provided the interventions in government-run primary health centers. Treatment effects were determined using longitudinal, multilevel models with CMHW and client as random effects, and a time by group interaction with robust variance estimation, to test for the net difference in mean score for each outcome between the baseline and follow up interview. Multiple imputation techniques were used to account for missingness at the item level and the participant level. All analyses were conducted using Stata 12. Results The CETA intervention showed large effect sizes for all outcomes. The CPT intervention showed moderate effects sizes for trauma and depression, with small to no effect for anxiety or dysfunction, respectively. Conclusions Both CETA and CPT appear to benefit survivors of systematic violence in Southern Iraq by reducing multiple mental health symptoms, with CETA providing a very large benefit across a range of symptoms. Non-specialized health workers were able to treat comorbid symptoms of trauma, depression and anxiety, and dysfunction among survivors of systematic violence who have limited access to mental health professionals. The trial further supports the use of evidence-based therapies in lower-resource settings. Trial registration and protocol This trial was registered at ClinicalTrials.gov on 16 July 2010 with an identifier ofNCT01177072 as the Study of Effectiveness of Mental Health Interventions among Torture Survivors in Southern Iraq. The study protocol can be downloaded from the following website:http://tinyurl.com/CETA-Iraq-Protocol . In the protocol, the CETA intervention is given a different name: components-based intervention or CBI.